Foreign Remittance and Economic Growth: An Empirical study from Nepal (SS Multidisciplinary Research Journal, 2025)
This research empirically explores how foreign remittances affect Nepal’s economic growth, using annual time-series data covering the period from 2001/02 to 2023/24. As one of the world’s largest recipients of remittances relative to GDP, understanding the role of remittances is crucial for Nepal’s economic policy. The study applies the Autoregressive Distributed Lag (ARDL) model to assess both short-term and long-term relationships. The results reveal a mixed effect: remittances have a statistically significant and positive impact on real GDP in the short run, but this effect becomes insignificant over the long run. On the other hand, gross private capital formation, government expenditure, and exports are found to be strong and significant contributors to long-term economic expansion. The study concludes that while remittances remain an important source of income and stability, excessive reliance on them cannot ensure sustained economic growth. Therefore, policymakers should aim to create a conducive environment for productive investment and strengthen the core drivers of long-term development.